Cooperative Abilities and Cognitive Learning Outcomes: Study Group Investigation on Life Cycle Topic - Leasa, Marleny; Marthina Eralisa Wuarlela (International Journal of Elementary Education, 2023)
The cooperative ability and cognitive learning outcomes of students in Ambon City still need to improve. The results of students learning science evidence this. The solution that can be done is to use learning models that can stimulate the development of students' cooperative and cognition abilities, one of which is group investigation. This study aims to analyze the relationship between cooperative abilities and cognitive learning outcomes in science learning with the GI cooperative model. The type of research used is correlational, with a sample of 50 people. The data collection instruments used in this study included questionnaires on students' collaboration abilities and cognitive learning outcomes test instruments—data analysis using simple linear regression. The results showed the sufficient category was the relationship between cooperative abilities and students' cognitive learning outcomes in science content learning the life cycle material with the Group Investigation type cooperative model. It was also revealed that the contribution of the cooperative ability variable to cognitive learning outcomes proves that GI contributes to students' cooperative abilities and cognitive learning outcomes.